ANALISIS PELAYANAN PEDAGANG TERHADAP KONSUMEN DI TINTAU DARI ETIKA BISNIS ISLAM (Studi Kasus Toko Sembako di Kelurahan Ganjar Asri) - Puspitasari, Synthia; Mentino, Dofriyansyah; Renfiana, Lilis (Al-Idarah, 2024)
Service quality is a strategy that is used to attract consumers which is applied so that the desire to create satisfaction for consumers is realized. If the quality of service in each business is carried out well, this will provide a positive outlook and can increase consumer buying interest. But humans need to remember that not all resources can be used because humans are bound by ethics. Islam teaches its adherents to be guided by Islamic teachings or Islamic business ethics, including when it comes to doing business. This research is descriptive qualitative in nature using interviews, documentation and observational data collection techniques. With the aim of finding out which shop has the best service quality. Based on the research results and discussions in the research, 2 shops have been found that fit the criteria, namely Bu Dwi Shop and Syifa Shop. It can be concluded that Toko Bu Dwi has implemented the principles of Islamic business ethics well, namely by implementing the principles of free will, responsibility, monotheism and ihsan. Meanwhile, the Syifa Shop cannot fulfill the principles of Islamic business ethics properly because the shop can only fulfill the three principles of free will, responsibility and ihsan.